ASAS AKUNTABILITAS DALAM PENDAFTARAN TANAH SISTEMATIS LENGKAP BERDASARKAN PERATURAN MENTERI AGRARIA DAN TATA RUANG / KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 6 TAHUN 2018 - Aisyah Silvi Kurniawati (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTEnforcement of Systematic and Complete Land Registration (PTSL) is carried out by the State Operator. Every act of state administrators related to PTSL must be accountable to the public and must be guided by the Principle of State Administrators, one of which is the principle of accountability. The principle of accountability is closely related to the accountability of the organizers in carrying out their duties. The purpose of this study is to find out whether there is the principle of accountability and how the legal consequences of the principle of accountability in PTSL based on ATR Regulation / Head of BPN No. 6 of 2018. The analytical method used in this study is a normative juridical approach to the law, conceptual approach and case approach. The principle of accountability exists and is proven to be applied in a Complete Systematic Land Registration Based on ATR Minister Regulation / Head of BPN No. 6 of 2018. The existence of the application of the principle of accountability in Complete Systematic Land Registration based on ATR Ministerial Regulation / Head of BPN No. 6 of 2018 brings legal consequences as the fulfillment of elements in the legal objectives which fulfill the elements of justice, usefulness and legal certainty.Keywords : Legal Consequences, Principle of Accountability, Complete Systematic Land Registry ABSTRAKPelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) dilaksanakan oleh Penyelenggara Negara. Setiap perbuatan penyelenggara negara yang berkaitan dengan PTSL ini harus dapat dipertanggungjawabkan kepada masyarakat serta harus berpedoman pada Asas Penyelenggara Negara salah satunya adalah asas akuntabilitas. Asas akuntabilitas ini erat kaitannya dengan pertanggungjawaban penyelenggara dalam mengemban tugasnya. Tujuan penelitian ini yaitu mengetahui adakah asas akuntabilitas dan bagaimana akibat hukum adanya asas akuntabilitas dalam PTSL berdasarkan Permen ATR/ Kepala BPN No. 6 Tahun 2018. Metode analisis yang digunakan dalam penelitian ini adalah yuridis normatif dengan pendekatan undang-undang, pendekatan konseptual dan pendekatan kasus. Asas akuntabilitas telah ada dan terbukti diterapkan dalam Pendaftaran Tanah Sistematis Lengkap Berdasarkan Permen ATR/ Kepala BPN No. 6 Tahun 2018. Adanya penerapan asas akuntabilitas dalam Pendaftaran Tanah Sistematis Lengkap berdasarkan Permen ATR/ Kepala BPN No. 6 Tahun 2018 membawa akibat hukum sebagaimana terpenuhinya unsur-unsur yang ada pada tujuan hukum yang mana memenuhi unsur-unsur keadilan, kemanfaatan dan kepastian hukum.Kata Kunci : Akibat Hukum, Asas Akuntabilitas, Pendaftaran Tanah Sistematis Lengkap